Counteracting the effects of TNF receptor‐1 has therapeutic potential in Alzheimer's disease. Issue 4 (22nd February 2018) - Steeland, Sophie; Gorlé, Nina; Vandendriessche, Charysse; Balusu, Sriram; Brkic, Marjana; Van Cauwenberghe, Caroline; Van Imschoot, Griet; Van Wonterghem, Elien; De Rycke, Riet; Kremer, Anneke; Lippens, Saskia; Stopa, Edward; et al.
Abstract: Alzheimer's disease (AD) is the most common form of dementia, and neuroinflammation is an important hallmark of the pathogenesis. Tumor necrosis factor (TNF) might be detrimental in AD, though the results coming from clinical trials on anti‐TNF inhibitors are inconclusive. TNFR1, one of the TNF signaling receptors, contributes to the pathogenesis of AD by mediating neuronal cell death. The blood–cerebrospinal fluid (CSF) barrier consists of a monolayer of choroid plexus epithelial (CPE) cells, and AD is associated with changes in CPE cell morphology. Here, we report that TNF is the main inflammatory upstream mediator in choroid plexus tissue in AD patients. This was confirmed in two murine AD models: transgenic APP/PS1 mice and intracerebroventricular (icv) AβO injection. TNFR1 contributes to the morphological damage of CPE cells in AD, and TNFR1 abrogation reduces brain inflammation and prevents blood–CSF barrier impairment. In APP/PS1 transgenic mice, TNFR1 deficiency ameliorated amyloidosis. Ultimately, genetic and pharmacological blockage of TNFR1 rescued from the induced cognitive impairments. Our data indicate that TNFR1 is a promising therapeutic target for AD treatment. Synopsis: Increased TNF/TNFR1 signaling plays a detrimental role in Alzheimer's disease pathology and is associated with morphological alterations at the choroid plexus in patients and mice, and neuroinflammation. Blocking TNFR1 signaling prevents cognitive decline in Alzheimer's disease mouse models. TNF/TNFR1 signaling is activated in the choroid plexus of late‐stage Alzheimer's disease patients. Increased TNFR1 signaling contributes to morphological alterations in choroid plexus epithelial cells. TNFR1 deficiency prevents neuroinflammation and amyloidogenesis, and reduces microgliosis in Alzheimer's disease mouse models. Genetic and pharmacological blockage of TNFR1 signaling prevents cognitive decline in Alzheimer's disease mouse models. Abstract : Increased TNF/TNFR1 signaling plays a detrimental role in Alzheimer's disease pathology and is associated with morphological alterations at the choroid plexus in patients and mice, and neuroinflammation. Blocking TNFR1 signaling prevents cognitive decline in Alzheimer's disease mouse models.